1997
DOI: 10.2307/3433244
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Risk Factors for Asthma and Wheezing among Seattle School Children

Abstract: Indoor risk factors for physician-diagosed asthma and w in the past 12 months without previous asthm diagnosis we asseed in a survey of parents of 5-9-year-old Seatde pimary school stuents. Among the 925 repndts, 106 (11%) reported a phy diagnosis of asthma, 66 (7%) had wheezing without danis, and 753 (82%) we mptmc. After adjusting for age, gender,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(54 reference statements)
3
4
0
Order By: Relevance
“…Thirty-one percent (31%) of families in this study reported to have condensation on windowpane in winter. This is consistent with a prior study in Seattle, which showed that 34% of 925 participating families reported to have water condensation [20]. However, we found less mould/mildew spots in Northeast Texas families (18%) compared to those in Seattle (54%) and in Boston (38%) [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Thirty-one percent (31%) of families in this study reported to have condensation on windowpane in winter. This is consistent with a prior study in Seattle, which showed that 34% of 925 participating families reported to have water condensation [20]. However, we found less mould/mildew spots in Northeast Texas families (18%) compared to those in Seattle (54%) and in Boston (38%) [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that children and adolescents faced multiple types of residential and environmental exposures during their evacuation and return to New Orleans, thereby potentially compromising their respiratory health and suggesting an overall significant increase in URS and LRS after the storm. These findings echo those found in other studies, 4,10,11,23,25,26,29 providing additional self-reported information on a child-and adolescent-specific sample that is often missed in larger studies or focused outbreak investigations. Findings suggest that there is a relationship between environmental exposures and URS and LRS, which can be exacerbated by adverse exposures, and may be worse in children and adolescents with preexisting health conditions.…”
Section: Resultssupporting
confidence: 88%
“…12 Children are at an increased risk of developing respiratory conditions after exposure to mold, dust, allergens, and other irritants, including sewage. 10,[14][15][16][17][18][19][20][21][22][23][24][25][26] The purpose of this period cross-sectional study was to characterize associations between environmental and residential exposures and respiratory symptoms among a convenience sample of children and adolescents who sought care in the New Orleans metropolitan area immediately following Hurricane Katrina.…”
mentioning
confidence: 99%
“…This study indicates that the use of a fireplace or wood-burning stove was less prevalent in homes with child and adult cases than in homes of controls, even when adjusted for socioeconomic status and geographic region. While several studies found that having a fireplace or wood-burning stove was associated with higher asthma prevalence, [25][26][27] other studies found no association, 20,[28][29][30][31] and several have mentioned that some households with asthma may decrease or stop their use of a fireplace or wood-burning stove. 29,30 It is possible that our finding reflects changes in behavior (i.e., not using fireplaces or wood-burning stoves) in an effort to avoid asthma triggers.…”
Section: Discussionmentioning
confidence: 99%